‘Count me in’ exercise of child participation rights of former child representatives - Ilagan, Rinica Vanessa Grace R.; Rosales, Judy Ann R.
This study seeks to explore the experiences of former barangay-level child representatives, focusing on their participation in local governance. A total of 15 respondents were chosen through purposive sampling with two-on-one interviews. The semi-structured interview guide delved into their roles and responsibilities, barriers and recommendations of former child representatives to exercising child participation. Results of the study show that former child representatives took on roles and responsibilities such as participating in seminars and summits, attending in barangay meetings, and mediating on issues and needs of children. The barriers were also identified namely: parental restrictions, perceived disinterest in projects, programs and activities (PPAs), conflict of schedule, invalidation from older barangay officials, lack of opportunities for younger children and children with special needs, lack of encouragement from barangays, and lack of knowledge of children’s rights. With these, former child representatives recommended several points to exercising child participation. The participants suggested to have more tailored PPAs to the needs and interests of children, to educate adults and children about children’s rights, and proper dissemination of information regarding PPAs. With the help of Lundy’s Model of Child Participation, findings suggest that there is a need for improvement on the implementation of child participation in the country in terms of local governance.